2012
DOI: 10.1021/la301760a
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Assembly and Disassembly of Micelles by a Polymer That Switches between Hydrophilic and Hydrophobic Wettings

Abstract: Supramolecular complexes involving nanoscopic amphiphilic assemblies (AAs) and polyelectrolytes have been used to prepare a variety of materials, wherein the dynamic AAs retain the structural features, but the polyelectrolytes undergo conformational changes. Here we show that a charge bearing rigid conjugated polymer can alter the structural features and disassemble AAs. We also demonstrate reversible assembly and disassembly of AAs by controlling the number of charges on the rigid polymer. During the disassem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…The surfactants influence the physical properties (morphology, solubility) of the resultant polymer [32]. It has been reported that nanotubes of hydrophobic interiors were prepared by disassembling anionic micelles in the inner walls of positive charge bearing conjugated polymer [33]. It was also studied that supramolecular complexes involving nanoscopic amphiphilic assemblies (AAs) and polyelectrolytes have been used to prepare a variety of materials, wherein the dynamic AAs retain the structural features [34].…”
Section: Introductionmentioning
confidence: 99%
“…The surfactants influence the physical properties (morphology, solubility) of the resultant polymer [32]. It has been reported that nanotubes of hydrophobic interiors were prepared by disassembling anionic micelles in the inner walls of positive charge bearing conjugated polymer [33]. It was also studied that supramolecular complexes involving nanoscopic amphiphilic assemblies (AAs) and polyelectrolytes have been used to prepare a variety of materials, wherein the dynamic AAs retain the structural features [34].…”
Section: Introductionmentioning
confidence: 99%
“…TEM images of a) PAni NFs and b) PAni NWs , . Reproduced by permission of The American Chemical Society and The Royal Society of Chemistry, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Polymerization of aniline was performed at the interface of an aqueous layer containing hydrochloric acid (HCl, reagent grade, LobaChemie) and the oxidant ammonium peroxodisulfate (APS, Sigma Aldrich), and an organic layer containing aniline monomer (Sigma Aldrich) [27][28][29]. The ratio of the reagent used was aniline:APS:HCl = 1:1:2.…”
Section: Synthesis Of Pani Nfs and Nwsmentioning
confidence: 99%
“…The unremitting research endeavor on the architecture of polymeric micellar assemblies exhibit potentials for enhanced stability . However, the undesirable release caused by dilution or interaction with the biological components largely restricted the biomedical application …”
Section: Introductionmentioning
confidence: 99%